Relationship of Regional Government and Village Government Before and After the Effect of Law Number 6 of 2014 Concerning Villages - Prasetiawan, Andik; Muhibbin, Moh. (Ridwan Institute, 2024)
The relationship between local and village governments becomes uncertain and blurs from its essence. In addition to exercising the remaining authority of the Regional Government although not herarchically but formalistically, the existence of the Village as a legal community unit that has original autonomy based on the right of origin is not fully recognized. As a unitary state, Indonesia recognizes and respects the existence of villages and customary villages, which are referred to as